ECONOMIC SECURITY AND VECTORS CHANGE OF ENTAERPRISES’ EXPORT ORIENTATION UNDER THE INFLUENCE OF GLOBALIZED TRANSFORMATIONS OF INTERNATIONAL TRADE - SAVITSKYI, Andrii; SHARKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article updates the issue of ensuring the economic security of enterprises, taking into account the change in the vectors of their export orientation, caused by tariff fluctuations in international trade. The key macroeconomic and global factors of influence on the internal environment and external conditions for Ukrainian producers have been identified. The impact of tariffs changes on country’s economic Gross Domestic Product and inflation growth, stability of market structures in international relations has been detailed. Taking into consideration tariffs rates, the current state of tariff transformations and the consequences of the tariff policy of developed countries for the economic systems of other developing countries has been analyzed. The global volumes of production predictions and its fluctuations, especially in Gross Domestic Product account have been presented. Based on the analysis of international trade indicators (exports, imports, trade balance) of Ukraine in the global dimension, USA, European Union and Asian countries in particular, the situation in which Ukrainian export-oriented producers found as of 2025 has been characterized. By the results made with analysis and interpretations, the main opportunities that are being formed for Ukrainian foreign economic activity entities in the direction of expanding their exports have been established and detailed. The most appropriate directions through substitution of supplement in the USA market, making an advantage in industrial chains, strengthening positions in food exports, usage of intermediary potential in global trade flows, creating a cluster specializations of export products focused on specific market segments have been interpreted. On the basis of defining groups of indicators, responsible parties and instrumentation for making adoptive positions, the management elements of algorithm of actions to insure economic security of exporting enterprise of Ukraine under conditions of changes in the tariff policy of developed countries have been proposed and systematized.
Keywords: tariff policy; economic security; international trade; export; import; trade balance; export-oriented enterprises; management